Strategic Planning for Islamic Educational Institutions in the Globalization Era - Muhammad Ali Murtadho; Ridho Dwi Putra; Fauza Yanuarti Pertiwi; Muhammad Sirozi (Yayasan Sembilan Pemuda Indonesia, 2026)
Islamic educational institutions face complex challenges in the globalization era, including technological disruption, intense competition, and demands for adaptive yet values-based graduates. Strategic planning offers a potential solution, yet its integration with Islamic educational values remains underexamined. This study examines how strategic planning can address development challenges faced by Islamic educational institutions in the globalization era. A qualitative library research method was employed, analyzing 45 academic sources (books, peer-reviewed articles, policy documents) using thematic content analysis. The analytical framework integrated SWOT analysis with Islamic educational principles. Findings indicate that strategic planning addresses five key challenges: (1) human resource quality through continuous competency-based training; (2) institutional governance through systematic planning and evaluation; (3) Islamic value integration through curriculum and co-curricular alignment; (4) funding sustainability through resource optimization and partnerships; (5) graduate competitiveness through 21st-century skills development. SWOT analysis emerged as a relevant tool for context-sensitive planning. This study integrates modern strategic management concepts (SWOT, performance measurement) with Islamic educational values into a comprehensive conceptual framework. Policymakers and institutional leaders should implement systematic, values-based strategic planning to enhance institutional competitiveness while preserving Islamic identity.